An evolutionary model of firms location with technological externalities - Giulio Bottazzi; Pietro Dindo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2008)
In an economic geography model where both a negative pecuniary and a positive technological externality are present, we introduce an explicit dynamics of firms locational choice and we characterize its long run distribution. Our analysis shows that economic activities evenly distribute when the pecuniary externalities prevail, and agglomerate otherwise. Due to the stochastic nature of the dynamics, even when agglomeration occurs, it is only a metastable state. By giving time and firms heterogeneity a role, we are bringing the evolutionary approach inside the domain of economic geography.
Keywords: C62; F12; R12; 330; Evolutionary Economic Geography; Heterogeneity; Agglomeration; Technological externalities; Markov Chains